Comparative Study Between Direct Steam Generation and Molten Salt Solar Tower Plants in the Climatic Conditions of the Eastern Moroccan Region - Lahoussine Ouali, Hanane Ait; Moussaoui, Mohammed Amine; Mezrhab, Ahmed; Naji, Hassane (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
This study deals with a numerical investigation to assess and compare the thermal and economic performance of two solar tower power systems. It concerns the Molten Salt (MS) and Direct Steam Generation (DSG) technologies used as heat carrier and storage. For this purpose, a 50 MWe solar tower plant without thermal energy storage under the climatic conditions of the eastern Moroccan region is simulated with the System Advisor Model (SAM) software. The meteorological data has been collected via a high precision meteorological station located in Oujda city(34°40'53'' N 1°54'30.9'' W). The results are presented in terms of monthly energy production, annual energy output, and Levelized Electricity Cost (LEC). From these findings, it can be concluded that, for an amount annual Direct Normal Irradiance (DNI) of 1989.9 kWh/m2/yr, the molten salt plant has the highest annual energy production than the DSG (86.3 GWh for MS against 83.3 GWh for DSG) and the LEC of the Molten salt plant is 12.5 % lower than the DSG plant.